Internet censorship detected in Oman (Oman) - Voidly (Voidly Global Censorship Index, 2026)
CRITICAL severity censorship detected in Oman. Data sourced from CensoredPlanet.
Censorship Incident ID: OM-2026-0060. Severity: critical. Confidence: 65%